DENDROLOGICAL DESCRIPTION AND ARCHITECTURE OF THE LEAF VENATION PATTERN OF THREE SPECIES BELONGING TO THE FABACEAE FAMILY - da Silva Moura, Alice Gabrielly; Viana de Souza, Andressa Jaqueline; Vieira, Thiago Almeida; Felsemburgh, Cristina Aledi (Floresta, 2024)
Dendrological Description and Architecture of the Foliar Venation Pattern of Three Species Belonging to the Fabaceae Family. Dendrological studies and means of diaphanization can help in the manipulation of species in the field, with the practice of management. The objective of this study was to describe the macromorphological characters and leaf venation of the species Copaifera martii, Dalbergia spruceana, and Libidibia ferrea. The characterization was carried out using a dendrological form, the trunk and leaves were evaluated, and the description of the venation was made through the diaphanization technique. It was observed that the Copaifera martii species supporting the live bark, initially beige changing to dark orange, leaves of leathery consistency, craspedodromous venation pattern, and marginal fimbrial venation. Dalbergia spruceana oxidized from yellowish-cream to red presented a resin-type exudate, leaf branches with lenticels and stipules, brochidodromous venation pattern, and recurved marginal venation. Libidibia ferrea presented bark detachment, a smooth and spotted rhytidome, grayish color, pulvinules and lenticels in all branches, and scalloped, brochidodromous pattern with recurved marginal venation. The dendrological characteristics of the trunk, together with the leaf and venation architecture, can augment taxonomic studies for the identification and differentiation of taxa.